BRAND AS A SYSTEM OF CONSERVATION, REPRODUCTION AND TRANSMISSION OF INFORMATION - Hrynevych, Viktoriya (Східноєвропейський національний університет імені Лесі Українки, 2019)
A powerful brand is the most valuable assert of any company. However, creation of a brand and raising of its valuability is a long and complex process not only within traditional marketing but also beyond it. A really popular brand cannot be created only by means of mass advertising or numerous proclamations. The emotion part always prevails in the image of a brand; its main resources are consumers’ trust, human values and positive associations.
Keywords: brand; advertisement; information conservation; information transmission